Estudo de interação da proteína Spike de SARS-CoV-2 ancestral e variantes com nanopartícula de prata associada ao flavonoide hesperetina - Dinis, Giulia Viana [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The SARS-CoV-2 virus was responsible for the largest global public health emergency in recent history and remains a concern due to its high variability and transmissibility. It is essential to incorporate strategies that make daily life safer regarding SARS-CoV-2 and its variants, particularly through the search for ligands capable of preventing viral infectivity. Silver nanoparticles functionalized with hesperetin (AgNP-HST) have proven to be highly effective antiviral agents, but the molecular mechanism underlying this activity remains unknown. Among the potential viral targets that may serve as the interaction site, the Spike protein, a trimeric glycoprotein located on the viral membrane and responsible for mediating cell invasion through interaction with the ACE2 receptor (angiotensin-converting enzyme 2) stands out. In this context, the present study aimed to characterize the interaction between SARS-CoV-2 Spike proteins from the ancestral Wuhan strain and variants (D614G, Gamma, Delta, and Omicron) with AgNP-HST. To achieve this, UV-Vis and Circular Dichroism spectroscopic experiments were performed to determine the dissociation constants (Kd) of the Spike/AgNP-HST complex, the thermodynamic profile of the interaction, and possible changes in secondary structure. Based on the Kd values, the following affinity order was established: D614G > Delta > Wuhan > Omicron > Gamma, and the D614G variant was selected for thermodynamic characterization due to its higher affinity. Thermodynamic analysis was carried out through UV-Vis titration experiments conducted at 15, 25 e 35 ºC, enabling the determination of enthalpy (ΔH), entropy (ΔS), and Gibbs free energy (ΔG) variantion, which indicated that the Spike/AgNP-HST interaction is driven primarily by electrostatic forces. Circular Dichroism (CD) results showed no significant structural changes upon complex formation. Therefore, this work demonstrated the interaction between silver nanoparticles functionalized with hesperetin and the SARS-CoV-2 Spike protein, corroborating the understanding of the biomolecular mechanism of the antiviral activity of the nanoparticles, based on blocking SARS-CoV-2 infection at the cellular level.
Study of the interaction of the Spike protein of ancestral SARS-CoV-2 and variants with a silver nanoparticle associated with the flavonoid hesperetin
Keywords: COVID-19 (Doença); Spike; Nanopartículas; Agentes antivirais; Biofísica; Biophysics; Antiviral agents; COVID-19 (Disease); Nanoparticles